Are you happy for me? how sharing positive events with others provides personal and interpersonal benefits.[article]. - Reis, Harry T.
Sharing good news with others is one way that people can savor experiences while building personal and interpersonal resources. Although prior research has been established the benefits of this process, called capitalization, there has been research and no experiments to examine the underlying mechanisms. In this article, we report results from 4 experiments and 1 daily diary study conducted to examine 2 mechanisms relevant to capitalization : that sharing good news with others increases the perceived value of those events, especially when others respond enthusiastically,and that enthusiastic responses to shared good news promote the development of trust and a prosocial orientation toward the other. These studies found consistent support for these effects across both interactions with strangers and in everyday close relationships. -- (from the author)